Hysterectomy in gestational trophoblastic neoplasia: Chiang Mai University Hospital's experience - Suparuek Pongsaranantakul (2018)
Indications and outcomes of hysterectomy in women with gestational trophoblastic neoplasia (GTN) were reviewed at Chiang Mai University Hospital, Chiang Mai, Thailand. From January 1998 through December 2008, 18 women underwent simple transabdominal hysterectomy (TAH). Indications for TAH included suspicious lesions confined to the uterus (5), chemoresistant lesions confined to the uterus (7), hemoperitonium (4), and other diagnoses of gynecologic diseases (2). The final histology reports included choriocarcinoma (9), invasive mole (6), placental site trophoblastic tumor or PSTT (1), uterine fibroid without residual GTN (1), and unknown (1). Two women experienced massive blood loss (4700 ml and 7500 ml, respectively). Postoperatively, only one woman with diagnosis of PSTT did not receive other adjuvant treatment. One woman failed to survive. In conclusion, hysterectomy continues to be an important treatment strategy for selected women with GTN. The common indications include drug-insensitive disease, PSTT, and hemorrhagic complications.